(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The teaching of music is not only about the technical transmission of musical knowledge but also about engaging students in a meaningful and interactive process that fosters creativity, emotional development, and critical thinking. Interactive methods in music education encourage active participation from students, facilitating a deeper understanding of musical concepts, improving skills, and enhancing students’ appreciation for music. This paper explores the significance of interactive methods in music lessons, examining their impact on student learning and the strategies that can be used to integrate these methods effectively into teaching. It discusses various interactive teaching techniques, such as group discussions, musical games, peer feedback, and technology integration, while highlighting the benefits of active engagement in the learning process. The research also includes a review of case studies and examples from music education to illustrate the successful implementation of interactive methods.